Composition and Evolution of the Labor Informality in Colombia During 2009-2019 - Ariza, John; Retajac, Floro Alexander (Universidad Pedagógica y Tecnológica de Colombia, 2021)
This paper studies the evolution and composition of informal employment in the main cities of Colombia during the period 2009-2019. Using bivariate and multinomial logit models, the probability of being informal and of belonging to the different categories of informal employment based on sociodemographic and economic characteristics is studied. The results indicate that during the period studied, labor informality fell both at the national level and in the main cities of the country, except for Cúcuta, and that such decrease did not have any specific pattern in terms of the composition of the informal workers. Informal workers in Colombia are mainly men with an average age of 40 years with less than 10 years of schooling who work mainly in commerce, industry and transportation. In recent years, both the average age and the years of schooling of this group in general have been increasing. The econometric results suggest a positive effect of education on informality at the local level that could explain the reduction in regional informality gaps.